Modulation of Dengue Virus Infection in Human Cells by Alpha, Beta, and Gamma Interferons - Diamond, Michael S. (American Society for Microbiology, 2000)
A role for interferon (IFN) in modulating infection by dengue virus (DV) has been suggested by studies in DV-infected patients and IFN receptor-deficient mice. To address how IFN modulates DV type 2 infection, we have assayed IFN-α, -β, and -γ for the ability to enhance or diminish antibody-independent and antibody-dependent cell infection using a competitive, asymmetric reverse transcriptase-mediated PCR (RT-PCR) assay that quantitates positive and negative strands of viral RNA, a flow cytometric assay that measures viral antigen, and a plaque assay that analyzes virion production. Our data suggest that IFN-α and -β protect cells against DV infection in vitro. Treatment of hepatoma cells with IFN-α or -β decreases viral RNA levels greater than 1,000-fold, the percentage of cells infected 90 to 95%, and the amount of infectious virus secreted 150- to 100,000-fold. These results have been reproduced with several cell types and viral strains, including low-passage isolates. In contrast, IFN-γ has a more variable effect depending on the cell type and pathway of infection. Quantitative RT-PCR experiments indicate that IFN inhibits DV infection by preventing the accumulation of negative-strand viral RNA.